DEVELOPMENT AND VALIDATION OF THE HAMI INSTRUMENT: A TOOL FOR EVALUATING TEACHERS"™ ETHICAL PRACTICES IN SCIENCE IDENTITY ASSESSMENT - Jayah, Johan Susanato; Wulan, Ana Ratna; Hamdiyati, Yanti (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to develop and validate the HAMI (Holistic Assessment for Measuring Science Identity) instrument, designed to evaluate the ethical practices that teachers use in assessing students"™ science identity. The research employed a Research and Development (R&D) approach, which included expert validation and two rounds of empirical testing. The first round involved 41 students, followed by Rasch analysis to ensure validity and reliability. The second round, with 304 students from six schools, confirmed the instrument's robustness across diverse educational settings. The HAMI instrument consists of five core aspects: (1) Implementation of Science Identity Development in Teaching Practices, (2) Assessment of Science Identity, (3) Preparation of Ethical and Inclusive Assessments, (4) Fair and Supportive Assessment Implementation, and (5) Supportive and Developmental Feedback. Results showed that the instrument effectively measures the alignment of assessment practices with science identity development, adhering to ethical principles. The study highlights the importance of ethical assessments in fostering a positive science identity.